Behaviour of geomagnetic storm, horizontal geomagnetic field and solar wind parameters during solar flare and CMEs event. - Umar, R.; Syed Zafar, S.N.A.; Hazmin, S.N.; Jusoh, M.H.; Dagang, A.N.; Adzni, M.A.M. (2021)
Space weather is driven by solar activities by pulling out the variety of phenomenon such as solar flare and coronal mass ejection (CMEs). It been discovered the CMEs and solar flares have causes disturbance at near-Earth space. This paper is to examined the behaviour of geomagnetic storm, horizontal geomagnetic field and several solar wind parameters during solar flare and CMEs event at minimum of solar cycle of 24. Observational result found that association of strongest solar flare and CMEs have declined the geomagnetic storm until-150nt at 8th September 2017. Following to this, the H component reading also slightly decreased at three magnetometer location respectively. Solar flare and CMEs released the energetic particles that could disturbed the radio communications at the Earth and electronic equipment. Therefore, it was required to study and understanding the solar flare and CMEs event.